The interaction between suicidal ideation, insomnia symptoms, and student status. (23rd November 2021) - Ober, Teresa; Stevenson, Jodie C.; Irvine, Kamila; Allen, Sarah; Akram, Umair
Abstract: Evidence demonstrates increased vulnerability to thoughts and behaviors related to suicide (i.e., suicidal ideation) in students. This study examined the interaction between insomnia-symptoms and student-status (students vs. non-students) on reports of suicidal thoughts of behaviors. A total of 363 ( N  = 363) university students and 300 ( N  = 300) members of the general population provided complete data on measures of insomnia-symptoms and suicidal ideation. Students indicated greater reports of both total and lifetime ideation while also considering suicidal behavior within the past year. However, no differences were observed in reports of possible future attempt(s) and the disclosure of suicidal thoughts and behaviors to another person. Moreover, students presenting concurrent symptoms of insomnia reported significantly elevated levels of suicidal ideation relative to nonstudents. These outcomes highlight the possible role of insomnia symptoms in accentuating suicidal thoughts and behaviors in the student population.